IDENTIFIKASI BAHAN TAMBAHAN MAKANAN (BTM) BERBAHAYA (FORMALIN, RHODAMINE B, DAN BORAKS) PADA MAKANAN YANG BANYAK DIPERJUALBELIKAN DI PASAR ATAS KOTA CIMAHI - Rifa'atul Mahmudah, Gina; Rifqi Damayanti, Indira; Salsadila, Sabina; Nur Fajriah, Yusnia; Kautsar, Pascal; Syamsul Fauzan, Muhammad; Firdaus Apendi, Ahmad (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2023)
Background: One of the problems that often occurs in Indonesia is the widespread distribution of food that does not comply with food safety standards due to ignorance and public concern for food quality. Based on data obtained from the Food and Drug Supervisory Agency (BPOM), there are still many foods that contain several types of dangerous Food Additives (BTM), such as borax, formalin, and rhodamine B, which are prohibited for use. The low level of public knowledge and awareness regarding the dangers of Food Additives (BTM) means that there are no preventive efforts by the community in selecting food to be traded in the market. Purpose: This research aims to identify the content of formaldehyde, borax, and rhodamine B in foods that are widely traded in the Pasar Atas Cimahi. Method: The type of research used is experimental. Testing for the presence of borax, formalin, and rhodamine B in food samples was carried out at the Chemistry Laboratory of Jenderal Achmad Yani University, Cimahi. The sampling technique is simple random sampling with the criteria of food that is widely traded in the market and based on product packaging that does not have a brand, code label, or other data so that it is suspected of containing food additives (BTM) in the form of formalin, borax, and rhodamine B. Results: The 15 food samples identified did not contain borax, formalin, or rhodamine B. Conclusion: Negative results on a qualitative examination need to be tested with a more sensitive and specific examination. This is because the low levels of formalin, borax, and rhodamine B in food allow these additives to go undetected. Even so, preventive efforts must still be made by the community to choose the food that is traded in the market.